Meneguhkan Pendidikan Demokratis dan Multikultural untuk Membangun Karakter Inklusif Peserta Didik di Indonesia - Woro Yustia Pratiwi; Musa Asy’arie; Mahasri Shobahiya (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2026)
Abstract Indonesia is known as a nation of rich cultural, ethnic, religious, and linguistic diversity. This diversity represents a source of national strength but also poses challenges in promoting social harmony and democracy. Education plays a central role in fostering tolerance, empathy, and active participation as the foundation of a democratic society. This article aims to examine the interrelationship between democratic education and multicultural education in shaping inclusive character among Indonesian students. This study employs a literature review method, analyzing both national and international studies published between 2020 and 2024. The analysis adopts a descriptive-analytical approach to identify conceptual relationships, school-based implementation practices, and challenges in applying democratic and multicultural values. Findings indicate that integrating democracy and multiculturalism within the education system enhances students’ tolerance, social empathy, and reflective thinking skills. Moreover, democratic multicultural education aligns with Indonesia’s current education policies, particularly the Merdeka Curriculum and the Profil Pelajar Pancasila framework. The article concludes that the collaboration among teachers, schools, and communities is essential in developing students’ inclusive character within a pluralistic society.